The Effects of Green Accounting and Intellectual Capital on Firm Value with Profitability Moderation - Tamara Melati Sukma; Omi Pramiana (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2025)
This research discusses the role of Green Accounting and Intellectual Capital affect firm value, while moreover assessing profitability as a moderating variable. The analysis is conducted on mining firms listed on the Indonesia Stock Exchange for the 2023–2024 period. A quantitative design is applied, employing classical assumption testing, t-tests for significance, tests of the coefficient of determination, and Moderated Regression Analysis (MRA) to evaluate the impact of the independent variables on the dependent variable with the inclusion of a moderating variable. Data processing is carried out using SPSS. The study demonstrates that Green Accounting does not have a significantly influences firm value, whereas Intellectual Capital exerts a strong and significant positive effect. Profitability is found not to moderate the connection between Green Accounting and firm value, but it significantly enhances the influence of Intellectual Capital on firm value. Overall, the firm value of mining companies is predominantly shaped by Intellectual Capital, with profitability amplifying the value added by intellectual assets.